Severe Acute Hepatitis B Treated with Entecavir - Andrea Tosti; Alessio Sgrelli; Giuseppe Vittorio Luigi De Socio; Franco Baldelli (Mediterranean Journal of Hematology and Infectious Diseases)
Hepatitis B virus (HBV) infection constitutes a serious global health problem. Nowadays there are divergent data regarding the use of antiviral drugs to treat acute hepatitis B. We present here a case of a 62-year-old man affected by severe acute hepatitis B with progressive worsening of clinical and hepatic function. The patient was treated with entecavir without critical side effects. We observed rapid clinical and laboratory improvements and the disappearance of surface antigen (HBsAg). The treatment with entecavir was protracted until 17th week when the antibody antiHBs (anti HBs) appeared. Entecavir should be carefully considered for the treatment of severe acute hepatitis B cases.